Identifiability of lithium-ion battery electrolyte dynamics - Couto, LD; Drummond, R; Zhang, D; Kirk, T; Howey, DA (IEEE, 2022)
The growing need for improved battery fast charging algorithms and management systems is pushing forward the development of high-fidelity electrochemical models of cells. Critical to the accuracy of these models is their parameterisation, however this challenge remains unresolved, both in terms of theoretical analysis and practical implementation. This paper develops a framework to analyse from impedance measurements the identifiability of electrolyte dynamics—a subcomponent of a general Li-ion model that is key to enabling accurate fast charging simulations. By assuming that the electrolyte volume fractions in the electrode and separator regions are equal, an analytic expression for the impedance function of the electrolyte dynamics is obtained, and this can be tested for structural identifiability. It is shown that the only parameters of the electrolyte model that may be identified are the diffusion time scale and a geometric coupling parameter. Simulations highlight the identifiability issues of electrolyte dynamics (relating to symmetric cells) and explain how the electrolyte parameters might be identified.